The role of interventional radiology in complications associated with liver transplantation. Issue 12 (December 2015) - Ng, S.; Tan, K.A.L.; Anil, G.
Abstract : The evolution of liver transplantation (LT) from an unusual procedure to a practical therapeutic option for patients with life-threatening liver diseases has brought with it several unique challenges. Although the patient survival rates have been steadily improving, with more complex surgeries being performed and increasing duration of graft survival, the overall post LT complication rate continues to stay high. They include inflow complications related to portal vein (PV) or hepatic artery, outflow complications related to hepatic vein or inferior vena cava, biliary leaks or strictures, postoperative collections or abscesses, graft rejection or post-transplant malignancy. These post-transplant complications provide a fertile ground for interventional radiology (IR) to flourish as it can contribute towards the management of each of these, and on most occasions, except for in graft rejection, it can circumvent a major surgery or even re-transplantation. The minimally invasive nature and lower morbidity associated with IR procedures make them preferable to similar surgical procedures. In post-transplant biliary complications, IR and therapeutic endoscopy have almost completely replaced surgery as the first-line treatments. The same can be said regarding the important role that IR plays in the management of most non-acute vascular complications. Meanwhile, more evidence and experience needs to be accumulated in the endovascular treatment of acute vascular complications encountered in the early post-operative period. This review primarily focuses on the various IR strategies in the management of the LT-related vascular and biliary complications with illustrative cases.